Hubungan Tingkat Pengetahuan, Sikap Keselamatan Dan Kesehatan Kerja Dengan Perilaku Penggunaan Alat Pelindung Diri Studi dilakukan di PT. Pertamina (Persero) Integrated Terminal Manggis Tahun 2022 - Ni Wayan Anik Anggreani; Anysiah Elly Yulianti; Ni Ketut Rusminingsih; Nengah Notes (Poltekkes Kemenkes Denpasar, 2022)
Work accidents can be caused due to the low knowledge of workers about an occupational safety and health (K3) technique in the work environment. Various efforts have been made to prevent work accidents and protect workers with the use of personal protective equipment (PPE), but workers are still often found who do not comply with the use of PPE. The purpose of this study was to determine the relationship between the level of knowledge, K3 attitudes and the behavior of using PPE for employees of PT Pertamina (Persero) Integrated Terminal Manggis, this type of research is an analytical survey research with a cross sectional approach . The sample in this study were 33 people. The instruments used are questionnaires and observation sheets. The analysis was carried out using Fisher's exact test. Based on hypothesis testing, the level of knowledge of K3 with the behavior of using PPE, is indicated by a p-value of 0.000 where this result is 0.05. With the value of Coefficient Contingency = 0.667. and K3 attitudes with PPE use behavior are indicated by p-value 0.000 where this result is 0.05. With the value of Coefficient Contingency = 0.707, that is the level of a strong relationship. So it can be concluded that there is a relationship between knowledge, K3 attitudes and the behavior of using PPE for employees of PT. Pertamina (Persero) Integrated Manggis Terminal in 2022, it is hoped that PT. Pertamina (Persero) Integrated Terminal Manggis more closely supervises employees to use PPE completely.